ANALISIS TENTANG KEABSAHAN KEWENANGAN KEJAKSAAN NEGERI JAKARTA SELATAN DALAM PENYELESAIAN TUNGGAKAN IURAN JAMINAN BPJS KESEHATAN DI KOTA ADMINISTRASI JAKARTA SELATAN - nurul oktavia agri; Tatang Ruchimat (Fakultas Hukum Universitas Tarumanagara, 2021)
The Civil and State Administration Attorney's Office, the Prosecutor's Office with a Special Power of Attorney (SKK), can work for and on behalf of the state or government both within and outside the court. A state attorney is called a lawyer who represents the state and government in cases of civil and state administration (JPN). In its implementation, the state attorney is fully utilized by government agencies, State-Owned Enterprises (BUMN) and Regional-Owned Business Entities (BUMD) to defend their interests in civil and state administrative cases. The results of this study indicate that in the settlement of unpaid corporate dues Social Security Administrators (BPJS) give special powers to the prosecutor's office in handling civil cases and state administration.. Social Security Administration when compared to the handling carried out under the criminal procedure law. So that the authors draw the conclusion that the power of the Attorney as state lawyer in order to save the wealth of the State or in order to restore and protect the interests of the community and legitimate government authority based on a Special Power of Attorney representing BPJS Kesehatan to resolve problems related to Employers who are in arrears for Health insurance contributions.